Effectiveness of Percutaneous Coronary Intervention Versus Coronary Artery Bypass Grafting in Patients With End-Stage Renal Disease - Arta Pebrina; Agus Harsoyo (International Medical Journal Corp. Ltd, 2025)
Introduction: Coronary artery disease (CAD) is highly prevalent in patients with end-stage renal disease (ESRD), posing significant treatment challenges. Percutaneous Coronary Intervention (PCI) and Coronary Artery Bypass Grafting (CABG) are the main revascularization strategies, but their comparative effectiveness and safety in ESRD patients remain unclear. Methods: A comprehensive review of 13 studies, including randomized controlled trials, observational cohorts, and meta-analyses, was conducted. Studies were selected based on adult ESRD populations comparing PCI and CABG outcomes, focusing on mortality, major adverse cardiac events (MACE), repeat revascularization, quality of life, and complications. Results: Short-term mortality was consistently lower with PCI (e.g., 1.2% vs. 15.4% at 30 days in Wang et al., 2020). Acute renal failure incidence was also lower after PCI (2.3%) compared to CABG (7.7%) in CKD patients (Giustino et al., 2018). Long-term outcomes, including all-cause mortality and MACE, were generally comparable between PCI and CABG across multiple studies. However, in patients with diabetes and CKD, CABG showed superior 10-year survival (44.2% vs. 64.3% mortality; Gao et al., 2020). Repeat revascularization rates were often higher after PCI, though some studies reported similar complete revascularization success. Quality of life improvements were noted with PCI in early CKD stages but not in advanced stages. Discussion: PCI offers a safer short-term profile with fewer complications, while CABG may provide better long-term survival in select high-risk subgroups. Differences in complication profiles and patient comorbidities should guide treatment choice. Conclusion: Treatment decisions for ESRD patients with CAD should be individualized, balancing short-term safety and long-term benefits, ideally within a multidisciplinary framework.